Material witness - Chapman, Vannetta (Chapman, Vannetta. Shipshewana Amish mystery., 2012)
"Tragedy strikes on the opening night of the Fall Crafters' Fair when a woman is killed in the parking lot of Daisy's Quilt Shop, and the only witness is one of Melinda Byer's boys. The investigation takes a bizarre turn when detective Shane Black becomes convinced the killer was actually after Callie Harper"--Page 4 of cover.